CAREER INFORMATION IN CAREER GUIDANCE AND COUNSELLING - DASH, B. N.; NIBEDITA DASH (DOMINANT PUBLISHERS AND DISTRIBUTORS (P) LTD. 437814-B, MURARILAL STREET, ANSARI ROAD, DARYGANJ, NEW DELHI -110002, 2016)
This book provides detailed knowledge of the several dimension of career information in career guidance and counselling. It discusses the method of getting the collecting the occupational, personal and social information and describes aptitude test and job analysis as a source of information